Transoral Drug-Induced Sleep Endoscopy: A Useful Complementary Tool in Sleep Surgery - Ahmed Elsobki; Mohammed Elshaer; Hassan Ghabn; Mohamed E. El-deeb; Luci Suliman (International Archives of Otorhinolaryngology)
Introduction Drug-induced sleep endoscopy (DISE) is performed widely, and several studies have demonstrated its validity as it provides clinical information not available by routine clinical inspection alone.